Survey on Scheduling Algorithms for Multiple Workflows in Cloud Computing Environment - Aggarwal, A; Dimri, P; Agarwal, A (International Journal of Computer Sciences and Engineering, 2019)
Cloud computing has been the buzzword of the ICT industry lately and has been widely accepted because of its pay-as-you-go pricing model and ease of use. Hence the bigger scientific applications which are generally represented as workflow or DAG are also moving on the cloud. Scheduling workflows on the cloud was becoming a problem as the existing traditional workflow scheduling algorithms (for Grid) were not perfectly suitable for cloud environment because of its dynamic nature. This paper tries to explore the existing algorithms for scheduling multiple workflows in cloud computing environment and presents a comparative analysis in tabular form of some existing algorithms along with their parameters, methods and tools used.